2019
DOI: 10.30534/ijatcse/2019/122862019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction-Based Model for Student Dropouts using Modified Mutated Firefly Algorithm

Abstract: Academic database is considered as the heart and soul of every higher education institutions. This database contains a vast amount of useful information that is useful for analysis. Algorithms for machine learning play a significant role in mining academic databases and have been proven to be effective when applied in the academic field. Prediction models are made using relevant classification algorithms for dropout analysis. The success of the prediction model depends on the performance of the feature selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We also found that 16 studies proposed an improved academic prediction performance. When compared with others it turned out to have better accuracy than this one (Gamao and Gerardo, 2019;Yang and Li, 2018;Czibula et al, 2019;Popescu and Leon, 2018;Mansouri et al, 2021).…”
Section: Methods and Algorithms That Predict Academic Performancementioning
confidence: 86%
See 2 more Smart Citations
“…We also found that 16 studies proposed an improved academic prediction performance. When compared with others it turned out to have better accuracy than this one (Gamao and Gerardo, 2019;Yang and Li, 2018;Czibula et al, 2019;Popescu and Leon, 2018;Mansouri et al, 2021).…”
Section: Methods and Algorithms That Predict Academic Performancementioning
confidence: 86%
“…Most methods or algorithms for predicting academic performance are ML-based classification algorithms because they provide higher accuracy against other proposals (Rimadana et al, 2019;Gamao and Gerardo, 2019;Xu et al, 2019;Vora and Kamatchi, 2019;Tsiakmaki et al, 2020;Jayaprakash et al, 2020). These classification algorithms are mainly: Support Vector Machine (SVM), Naive Bayes (NB), Decision Trees (DT), Random Forests (RF), and Artificial Neural Networks (ANN).…”
Section: Methods and Algorithms That Predict Academic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Since its inception almost 15 years ago, FA and its modified variants have demonstrated significant success in various fields of application. For example, in multilevel image segmentation [3], as a way to reduce the number of dimensions [4], optimizing convolutional neural networks [5], solving course timetabling problems [6], and dealing with complex engineering tasks [7], [8], among other things. Knowing that FA has a universal application makes it a fascinating subject to pursue.…”
Section: Introductionmentioning
confidence: 99%